Frustrated Lewis pair-mediated fixation of CO2 within a metal–organic framework. Issue 73 (27th August 2019) - Shyshkanov, Serhii; Nguyen, Tu N.; Chidambaram, Arunraj; Stylianou, Kyriakos C.; Dyson, Paul J.
Abstract : We demonstrate the use of an in situ formed frustrated Lewis pair within MOF-545 to effectively hydrogenate CO2 to methoxide at a low temperature and pressure. Abstract : Finding pragmatic solutions to curb the accumulation of atmospheric CO2 and tackle the associated greenhouse effect is challenging. Herein, we demonstrate the use of an in situ formed frustrated Lewis pair (FLP) within a metal–organic framework (MOF) to effectively hydrogenate CO2 to methoxide at a relatively low temperature and pressure. The work presents a step toward the discovery of practical catalysts for CO2 reduction and conversion.